PD-L1 and ICOSL discriminate human Secretory and Helper dendritic cells in cancer, allergy and autoimmunity - Caroline Hoffmann; Floriane Noel; Maximilien Grandclaudon; Lucile Massenet-Regad; Paula Michea; Philemon Sirven; Lilith Faucheux; Aurore Surun; Olivier Lantz; Mylene Bohec; Jian Ye; Weihua Guo; et al. (Nature Communications, 2022)
Phenotypic and functional states of dendritic cells critically influence the outcome of cancer and inflammation. Authors here show by single cell transcriptomics and in vitro validation assays that dichotomous PD-L1 and ICOSL expression assign dendritic cells to secretory and helper functions, with respective predominance of inflammatory cytokine expression or T helper cytokine induction.